Forms of Care in Human–Nature–Technology Environments - Ciobanu, Patricia; Juhlin, Oskar (Journal of Posthumanism, 2022)
With the ongoing environmental disruptions, designers are increasingly interested in exploring nature–technology entanglements that create sustainable and collaborative futures. Although largely unarticulated, these emerging design inquiries are motivated by care for nature, which indirectly depends on cultural and social human practices. Drawing on a broad set of works on care from feminist theory, science and technology studies, and human–computer interaction, this article introduces a care framework that focuses on revealing tensions in the interrelationship between humans and nonhumans. The framework is used to examine an initial study in which five participants engaged with a speculative design probe, specifically a combination of a device and a plant, envisioning a scenario in which plants generate electricity. We reveal how forms of care manifest differently in a human–plant–technology dynamic and identify tensions, such as plants being considered utilities, proxies, or humans.